Qualitative evaluation of the Rehabilitation Exercise and psycholoGical support After COVID-19 InfectioN (REGAIN) randomised controlled trial (RCT): ‘you are not alone’ - Gordon McGregor; Susanne Finnegan; Martin Underwood; Joyce Yeung; James Mason; Peter Heine; Nigel Edwards; Julie Bruce; Kate Seers; Harbinder Kaur Sandhu; Helen Atherton; Sharisse Alleyne; et al. (BMJ Open)
Background This qualitative evaluation was embedded in the Rehabilitation Exercise and psycholoGical support After COVID-19 InfectioN (REGAIN) study, a randomised controlled trial (RCT) for those with post-COVID-19 condition (‘long COVID’) after hospital admission for COVID-19, comparing weekly home-based, live online supervised group exercise and psychological support sessions with ‘best practice usual care’ (a single session of advice).Objective To increase our understanding of how and why the REGAIN programme might have worked and what helped or hindered this intervention.Design A qualitative evaluation which utilised interviews with participants and practitioners delivering the intervention. Framework and thematic analysis were used to analyse the findings.Setting England and Wales, UK.Participants Adults discharged from National Health Service (NHS) hospitals at least 3 months previously after COVID-19, with ongoing physical and/or mental health sequelae.Results Twenty intervention participants, 20 control participants and five practitioners were interviewed.The themes from the group support sessions were: (1) you are not alone; (2) sharing experiences and addressing worries; (3) gaining new perspectives; (4) hope for progression; (5) peer support and bonding; (6) integration of facilitation skills; (7) modified activity pacing and goal setting, and (8) giving participants structure. The themes from group exercise were: (1) monitoring and modification of the online exercise; (2) catering for differing abilities; (3) feeling safe and confident to exercise; (4) progression of fitness; (5) optimal timing in the recovery trajectory; (6) group effect; (7) initial apprehension about exercise group; (8) gauging exercise capabilities; (9) translating exercises into life; and (10) on-demand supplementary videos. The 1:1 consultation sessions revealed patients needed to tell their stories.Conclusion Being listened to and being understood by someone ‘who got it’ was very important to people with post-COVID-19 condition. The group sessions of both exercise and psychological support were valued by participants, working together, and learning from each other in the face of a new disease within a global pandemic.